Kinetics of in vitro renin and angiotensin converting enzyme inhibition by chicken skin protein hydrolysates and their blood pressure lowering effects in spontaneously hypertensive rats. (April 2015) - Onuh, John O.; Girgih, Abraham T.; Malomo, Sunday A.; Aluko, Rotimi E.; Aliani, Michel
Highlights: Short-chain chicken skin peptides had better ACE inhibition than long-chain peptides. Kinetics of ACE and renin inhibition showed mainly mixed-type mechanism. The hydrolysates had the strongest blood pressure-lowering effect in spontaneously hypertensive rats. Blood pressure-lowering effect contrasted with observed in vitro ACE inhibition. In vitro renin inhibition was consistent with blood pressure-lowering effect. Abstract: Chicken skin protein hydrolysates (CSPHs) and their membrane ultrafiltration fractions were investigated for their blood pressure lowering effects. Chicken skins from thigh or breast muscles were hydrolyzed with 3% Alcalase or 1% pepsin/pancreatin, respectively; hydrolysates were then fractionated into <1, 1–3, 3–5, and 5–10 kDa peptide sizes. Chicken breast skin hydrolysate (CBSH) and peptide fractions inhibited angiotensin converting enzyme (ACE) with IC50 values of 0.36–0.64 mg/mL, which were significantly (p < 0.05) higher than the 0.42–0.75 mg/mL values obtained for chicken thigh skin hydrolysate (CTSH) and peptide fractions. Results suggest that a high content of branched-chain amino acids contributed to the significantly (p < 0.05) higher ACE-inhibition by <1 kDa peptide fraction. All the samples with exception of the CBSH 3 kDa fraction had similar renin inhibitory values. Kinetics studies revealed that enzyme inhibition pattern was mostly of the mixed-type for ACE and renin. Oral administration of 100 mg peptides/kg body weight to spontaneously hypertensive rats led to maximum systolic blood pressure reduction of −32.67 and −31.33 mmHg after 6 h for CTSH and CBSH, respectively. We conclude that the CSPHs have potential use as active ingredients to formulate antihypertensive functional foods and nutraceuticals.